Ten lectures on the elaboration of cognitive grammar - Langacker, Ronald W. (Distinguished Lectures in Cognitive Linguistics, 2017)
This book reviews the basic claims and descriptive constructs of Cognitive Grammar, outlines major themes in its ongoing development, and applies these notions to central problems in grammatical analysis.